2019
DOI: 10.1089/heq.2019.0048
|View full text |Cite
|
Sign up to set email alerts
|

Building Immigration-Informed, Cross-Sector Coalitions: Findings from the Los Angeles County Health Equity for Immigrants Summit

Abstract: In December 2017, the Los Angeles County Office of Immigrant Affairs and Board of Supervisors, alongside local health care and legal providers, convened the Health Equity for Immigrants and Families Summit to advance a vision for immigrant health. We describe the four critical concepts identified by stakeholders to address the varied needs of immigrants in an increasingly anti-immigrant political environment: (1) Recognizing immigration status as a modifiable social determinant of health; (2) Adopting the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Grassroots community coalitions are spaces where people with multiple intersecting identities and locations can come together and confront issues that affect and disempower the larger community collective (Enriquez, 2014). Research examining grassroots community coalitions highlights that these are versatile locations for leveraging resources, developing strategic partnerships, and transferring, as well as bridging resources in marginalized, segregated, financially‐strapped communities (Christens & Speer, 2015; Christens et al, 2019; Lardier et al, 2018; Saadi et al, 2019). Coalition‐based work, particularly for undocumented Hispanic/Latinx communities, creates space for individuals to develop and find meaning and ways to change the social circumstances that oppresses them (Chávez, 2011; Enriquez, 2014; Lardier et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Grassroots community coalitions are spaces where people with multiple intersecting identities and locations can come together and confront issues that affect and disempower the larger community collective (Enriquez, 2014). Research examining grassroots community coalitions highlights that these are versatile locations for leveraging resources, developing strategic partnerships, and transferring, as well as bridging resources in marginalized, segregated, financially‐strapped communities (Christens & Speer, 2015; Christens et al, 2019; Lardier et al, 2018; Saadi et al, 2019). Coalition‐based work, particularly for undocumented Hispanic/Latinx communities, creates space for individuals to develop and find meaning and ways to change the social circumstances that oppresses them (Chávez, 2011; Enriquez, 2014; Lardier et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…| 1661 marginalized, segregated, financially-strapped communities (Christens & Speer, 2015;Christens et al, 2019;Lardier et al, 2018;Saadi et al, 2019). Coalition-based work, particularly for undocumented Hispanic/Latinx communities, creates space for individuals to develop and find meaning and ways to change the social circumstances that oppresses them (Chávez, 2011;Enriquez, 2014;Lardier et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study highlights that asylum-seekers with PTSD or depression may be particularly vulnerable to these memory complaints and therefore represent a subset of the asylum-seeker population for whom memory issues need to be more closely assessed and attended to. Outside the legal context, clinicians should work towards promoting trauma-informed and immigration-informed models of care addressing trauma and associated cognitive complaints in their clinical work with this population [31]. There are also important distinctions that future, ideally prospective, research can elucidate upon, such as disentangling the diverse processes that underlie the relationship between traumatic events and memory gaps like dissociative amnesia or dissociation during a trauma that were alluded to in our qualitative analyses [32].…”
Section: Discussionmentioning
confidence: 99%
“…Addressing immigrant mental health must be done on both macro (structural/systems) and micro (personal/interpersonal) levels. Research has suggested that culturally-tailored and trauma-informed mental health training for diverse stakeholders can reduce negative effects associated with immigration and improve the adaptation experience in the settlement country (3,4). One study in the Research Topic examined the psychological effects of asylum interviews for asylum-seekers, which has a detrimental psychological impact on refugees.…”
Section: Addressing Immigrant Mental Health At Both the Macro And Micro Levelmentioning
confidence: 99%